2019
DOI: 10.1155/2019/1451490
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Force of Infection with Helicobacter pylori in Japan

Abstract: Background. Although the seroprevalence against Helicobacter pylori (H. pylori) in Japan has declined over the birth year, Japanese people have yet exhibited a relatively high risk of gastric cancer. The present study employed mathematical models to estimate the time- and age-dependent force of infection with H. pylori in Japan, predicting the future seroprevalence by time and age. Methods. We investigated the published seroprevalence data against H. pylori in Japan from 1980–2018. Solving the McKendrick parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Further projections of this trend for 2050 anticipate a further decline in the prevalence of H pylori and the incidence of gastric cancer. 17 Health professionals, in particular those working in gastrointestinal units, were found to have a higher risk; however, most of the studies date back two decades.…”
Section: Changing Prevalencementioning
confidence: 99%
“…Further projections of this trend for 2050 anticipate a further decline in the prevalence of H pylori and the incidence of gastric cancer. 17 Health professionals, in particular those working in gastrointestinal units, were found to have a higher risk; however, most of the studies date back two decades.…”
Section: Changing Prevalencementioning
confidence: 99%
“…Second, risk factors other than smoking were not explicitly considered. Genetic predisposition and well-known carcinogenic exposures could be used to attain earlier diagnosis and improve prognosis [47,48]. In fact, the relative risk of smoking in causing lung cancer among Japanese is known as smaller than those in the United States and Europe, referred to as the smoking paradox [49].…”
Section: Discussionmentioning
confidence: 99%
“…[18,[20][21][22]24] Despite such differences, our earlier study has shown that the observed antibody data over age and time, as extracted from all included studies, were well captured by a simple integral equation model and heterogeneity did not matter. [25] Using the collected dataset and estimating the hazard of infection [25], the best-fit model did not identify any age dependence in the hazard of infection, and estimated that the hazard of infection decreased over time beginning in the year 1937; the exponential decay in the hazard was 0.047 per year. [25] We used these published estimates and adopted the resulting prevalence of infection with H. pylori as a function of time and age.…”
Section: Epidemiological Datamentioning
confidence: 99%